Hominin heritage: How institutional repositories are managing collections, collaboration and repatriation - Wendy Black; Bernhard Zipfel; Mirriam Tawane; Glynn Alard; Phillip Hine (South African Journal of Science)
In this article, we discuss South African heritage management, and how it has shaped the role institutions play in protecting heritage 100 years ago versus today. Museums and universities are in a difficult position as they address past unethical archaeology and palaeoanthropology practices while implementing transformation and decolonisation approaches to protect and share heritage inclusively. We outline some of the complexities that museums, universities, and heritage bodies face in navigating human evolution research, site and material access, potential returns, repatriations or reburials, curation and the development of accessible educational content in a contemporary context.